MENILIK KEMBALI SEJARAH PEMIKIRAN EKONOMI ISLAM PADA MASA DAULAH MUGHAL - Harahap, Abdul Rahim (UIN Sumatera Utara Medan, 2023)
This study looks at the history of Islamic economic philosophy in the Mughal Empire. The Indian economy under the Mughal empire was a sophisticated system that lay the groundwork for future economic activities in the region. Exploring this time gives a better understanding of how agricultural and commerce routes influenced the Empire's success. Agriculture was the foundation of the Mughal economy. Shah Waliyullah Al-Dahlawi was an Islamic reformist thinker who flourished during the decline of the Mughal empire. He believes that because humans are innately social beings, they must work together. The cooperation in question may be commercial cooperation (mudharabah, musyarakah), agricultural management cooperation, and so on. Gambling and usury are examples of practices that violate the spirit of cooperation in Islam.